Nghiên cứu tổng hợp chọn lọc 10β-Azidoartemisinin - Vũ, Trần Khắc; Bình, Lê Huy; Bình, Nguyễn Thanh; Thúy Vân, Nguyễn Thị (Vietnam Journal of Chemistry, 2015)
This paper presents a simple method for selective synthesis of the key compound, 10β-azidoartemisinin. The compound 10β-azidoartemisinin was selectively synthesized by the reaction of dihydroartemisinin (2) with NaN3, KI using ZnCl2 as a catalyst at 0-5 oC. The structure of 10β-azidoartemisinin was elucidated based on 1H, 13CNMR spectrum and known documents.